EU and UN Development Cooperation: what should Germany work for? - Silke Weinlich; Sven Grimm (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Both the European Union and multilateral agencies in the United Nations (UN) system are important partners for German development policy. Roughly one third of the official development assistance (ODA) Germany provides is spent for multilateral development cooperation (DC). At the same time, multilateral DC has a chronically poor reputation, even though reforms are currently being carried out to address identified weaknesses. The UN system and the EU in particular have come in for criticism for the alleged inefficiency and lack of effectiveness of their policies as well as for duplications in their work. While European and multilateral DC is less accessible to control than bilateral assistance, it also has a number of concrete advantages over bilateral engagement. These latter include the size and scope of the programmes and a greater measure of neutrality as often perceived by partners. In other words, multilateral and bilateral DC can complement one another. Furthermore, Germany – like other countries – is reliant on a functioning multilateral system, both in terms of self-interest and as a means of contributing to meeting global challenges. The new German government should intensify its engagement in multilateral DC and support the EU and the UN in their efforts to refine their comparative advantages and to make better use of them. This would include an improved international division of labour and greater emphasis on orientation towards more effectiveness. Necessary reform measures should support the reform efforts from within the earmarked funds could be necessary. Successful reforms in the EU and the UN contribute more to improving the effectiveness of DC than national efforts ever could achieve on their own.
Keywords: 330